Spatiotemporal Changes in Water-Use Efficiency of China’s Terrestrial Ecosystems During 2001–2020 and the Driving Factors - Jia He; Yuxuan Zhou; Xueying Liu; Wenjing Duan; Naiqing Pan (Remote Sensing)
Water-use efficiency (WUE) is an important indicator for understanding the coupling of carbon and water cycles in terrestrial ecosystems. It provides a comprehensive reflection of ecosystems’ responses to various environmental factors, making it essential for understanding how ecosystems adapt to complex environmental changes. Using satellite-based estimates of gross primary productivity (GPP) and evapotranspiration (ET), our study investigated the spatiotemporal variations in WUE across China’s terrestrial ecosystems from 2001 to 2020. We employed the geographic detector method, partial correlation analysis, and ridge regression to assess the contributions of different factors (temperature, precipitation, solar radiation, vapor pressure deficit, leaf area index, and soil moisture) to GPP, ET, and WUE. The results show significant increases in GPP, ET, and WUE during the study period, with increase rates of 6.70 g C m−2 yr−1, 2.68 kg H2O m−2 yr−1, and 0.007 g C H2O m−2 yr−1, respectively. More than three-quarters of the regions with significant trends in WUE (p < 0.05) displayed notable increases in WUE (p < 0.05). Among all driving factors, leaf area index (LAI) made the largest contribution to WUE, particularly in warm temperate semi-humid regions. Precipitation and solar radiation were the primary climatic influences in arid regions of northern China and humid regions of southwestern China, respectively.